COMPARATIVE STUDY ON THE INTENSITY OF Mycobacterium leprae EXPOSURE TO CHILDREN WHO LIVE IN LOW AND HIGH ALTITUDE IN LOW LEPROSY ENDEMIC AREA OF SOUTH SULAWESI - Rachmawati, Rachmawati; Mataallo, Timurleng Tonang; Adam, Safruddin; Adam, A. M.; Amin, Safruddin; Tabri, Farida; Adriaty, Dinar; Wahyuni, Ratna; Iswahyudi, Iswahyudi; Agusni, Indropo (Institute of Topical Disease, 2013)
Background: The intensity of Mycobacterium leprae exposure to people who live in leprosy endemic area could be measured by serological study and detection of the bacilli in the nose cavity. Different geographical altitude might have some influences to this exposure since the bacilli prefer to live in warm areas. Aim: A combined serological and PCR study of leprosy was conducted in Selayar island, South Sulawesi to 80 school children (40 from low land and 40 from highland altitudes) in order to compare the exposure intensity between the two areas. Method: Anti PGL-1 IgM antibody (ELISA) and PCR study to detect M.leprae in the nasal cavity were performed simultaneously from each person. Result: Seropositive cases were found in 23/40 children from low land compared to 16/40 children from high land, but statistically no significant difference (p>0.05). PCR positive for M.leprae in the nasal cavity only found in 1/40 children, both in low and high altitude. Conclusion: It is concluded that although the existence of M.leprae in nasal cavity is minimal, the intensity of exposure to this bacilli still high as indicated by serological study.